Estimated Value For Diagnosis Of Hysterosonography Endometrial Polyp Cases In Women With Abnormal Uterine Bleeding In Maternal Perinatal Institute´S Gynecology Service, January 2009 - December 2011 - Tovar, Raquel Trinidad Orihuela (2019)
Objectives. Our goal is to determine the prevalence of endometrial polyps and estimate the diagnostic value of the HSG in the INMP. Materials and Methods.A cross – sectional study. The sample comprised patients attending the outpatient clinic of the Department of Gynecology, the reason for the visit is that of HUA in INMP in the period from January 2009 to December 2011. Inclusion criteria: non-pregnant patients with ultrasound scans an HSG in INMP, and then carried out two studies have a pathological study. The information is processed electronically with SPSS version 20,0 and Epidat 3,1. Be developed contingency tables and calculate the S, E, PPV and NPV of TV ultrasound and HSG, and their respective correlation.